2004
DOI: 10.1158/0008-5472.can-03-2807
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MSH3 Protein Expression Is Frequent in MLH1-Deficient Colorectal Cancer and Is Associated with Disease Progression

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 34 publications
(38 reference statements)
5
52
0
Order By: Relevance
“…Our results are also in agreement with the inverse relationship between clinicopathologic staging and accumulation of frameshift mutations observed in a large series of sporadic microsatelliteunstable cancers (42). In contrast, others (43) found an association between MSH3 loss and advanced tumor stage in a small group of MLH1-deficient CRCs, but the high rate of loss of heterozygosity suggests that that series was somehow enriched with tumors with overlapping patterns of microsatellite and chromosomal instability.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are also in agreement with the inverse relationship between clinicopathologic staging and accumulation of frameshift mutations observed in a large series of sporadic microsatelliteunstable cancers (42). In contrast, others (43) found an association between MSH3 loss and advanced tumor stage in a small group of MLH1-deficient CRCs, but the high rate of loss of heterozygosity suggests that that series was somehow enriched with tumors with overlapping patterns of microsatellite and chromosomal instability.…”
Section: Discussionsupporting
confidence: 91%
“…PMS2L3 has a similar function to that of PMS2 in MutL␣, which is to play a role in maintaining genome integrity via MMR and DNA damage-induced apoptosis [26]. Loss of MSH3 protein expression has been related to tumor progression in colorectal cancer [27]. Our finding that the MSH3 genetic variants contributed to shorter OS in patients with locally advanced or metastatic pancreatic cancer suggests that MSH3 deficiency may contribute to rapid tumor progression, possibly through accumulation of larger IDLs in patients with late-stage disease.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis revealed that MSH3 mutations gained strongly in signifi cance ( P = 7.43 × 10 −6 ) and activity effect (GI 50 ratio, 5.3) when restricted to protein structure-damaging microdeletions in the two longest mononucleotide/trinucleotide repeat sequences of the MSH3 coding sequence ( Fig. 1A and B (24)(25)(26)(27). Concordantly, we detected such mutations in our cancer cell line panel; 10 of 67 cell lines displayed microdeletions in the two longest mononucleotide/trinucleotide repeat sequences ( Fig.…”
Section: Activity Profi Le Of Ku60648 In a Large Panel Of Genomicallymentioning
confidence: 99%